Web-Based Inpatient Medical Record Review Information System Design Using the Agile Method: Implementation at RSUD Bandung City - Mely Fahmalia; Yuyun Yunengsih; Falaah Abdussalaam (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Inpatient medical record review is a major activity in ensuring the quality, completeness, and consistency of hospital healthcare documentation. Besides ensuring compliance with documentation standards, the review process also ensures that clinical services are accurately recorded for reference in future medical, legal, and administrative matters. This study aims to design a web-based information system that will facilitate structured, efficient, and integrated review workflows between medical record officers and other related units. The development of the system uses the Agile method which prioritizes flexibility and fast adaptation to user feedback so that improvements can be made iteratively. The prototype created can manage data input on reviews, generate summary results as well as reduce human errors usually found in manual entries. The hospital currently uses Google Spreadsheets and Google Forms which are tools with too many columns and prone to errors hence making tracking time and data inefficient. Usability testing using the System Usability Scale (SUS) obtained an average score of 68.13 which is categorized as “acceptable” usability indicating that the system is easy to use and feasible for real implementation. This system is then a basic solution for workflow simplification, validation accuracy improvement, and increasing documentation reliability of medical records in hospital environments.